Implementation of character values in project activities for Phase C primary school students in South Sulawesi - Rahma Ashari Hamzah; Sitti Mania; Andi Achruh; St. Syamsudduha (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study is to identify the implementation of character values through the execution of project activities, which serves as a case study for Phase C primary school students at SD Inpres 100 Dare Bunga-Bungae, Soppeng Regency, South Sulawesi. The research employed a qualitative descriptive approach, with data obtained from the principal, teachers, and students at the elementary school. Data were collected through interviews, observations, and documentation. Data analysis followed the Miles and Huberman model, which consists of four components: data collection, data reduction, data display, and conclusion drawing. The findings indicate that the project was implemented in accordance with the established guidelines, covering the introduction, contextualization, action, reflection, and follow-up stages. The character values reinforced through this project include faith and devotion to God Almighty, global diversity, collaboration, and creativity. The project's outcome was a performance of traditional dances from various regions, presented during the exhibition. Therefore, the project's implementation serves as a platform for elementary school students to develop their competencies and strengthen their character in line with the Pancasila student profile, ultimately contributing to achieving national education goals.